2021
DOI: 10.3390/diseases9020039
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Characteristics of Kidney Stones in Patients on Ketogenic Diet: A Systematic Review and Meta-Analysis

Abstract: Very-low-carbohydrate diets or ketogenic diets are frequently used for weight loss in adults and as a therapy for epilepsy in children. The incidence and characteristics of kidney stones in patients on ketogenic diets are not well studied. Methods: A systematic literature search was performed, using MEDLINE, EMBASE, and Cochrane Database of Systematic Reviews from the databases’ inception through April 2020. Observational studies or clinical trials that provide data on the incidence and/or types of kidney ston… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 82 publications
3
18
0
2
Order By: Relevance
“…Renal calculi have been reported in 3–7% of children on a ketogenic diet, consisting of both uric acid and calcium [ 13 , 57 , 58 , 59 , 60 ]. In addition, three studies of over 200 children on a KD, showed that potassium citrate led to a reduced incidence of renal calculi [ 58 , 61 , 62 ].…”
Section: Complications Of a Ketogenic Diet By Systemmentioning
confidence: 99%
“…Renal calculi have been reported in 3–7% of children on a ketogenic diet, consisting of both uric acid and calcium [ 13 , 57 , 58 , 59 , 60 ]. In addition, three studies of over 200 children on a KD, showed that potassium citrate led to a reduced incidence of renal calculi [ 58 , 61 , 62 ].…”
Section: Complications Of a Ketogenic Diet By Systemmentioning
confidence: 99%
“…eir prevalence in adults using KD is about 7.9% [43]. Current reports still do not provide complete data to determine whether the long-term regimen of carbohydrate intake demonstrated over periods of 5, 10, and 15 years is safe.…”
Section: Discussionmentioning
confidence: 99%
“…Using KD requires constant health monitoring as well as selecting proper macronutrients and hydration, due to the possible occurrence of disorders such as kidney stones. Their prevalence in adults using KD is about 7.9% [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…37 In one meta-analysis including 2795 patients on a ketogenic diet, the incidence of stone disease was about 6%. 38 Interestingly, the majority (w50%) of stones consisted of uric acid, than approximately 40% calcium-containing stones and the rest being mixed, likely reflecting low urine pH, a key risk factor for uric acid precipitation.…”
Section: Etiologymentioning
confidence: 99%